2008
DOI: 10.1002/bmc.1059
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of phenibut in rat brain tissue extracts by liquid chromatography–tandem mass spectrometry

Abstract: Phenibut (3-phenyl-4-aminobutyric acid) is a gamma-aminobutyric acid mimetic drug, which is used clinically as a mood elevator and tranquilizer. In the present work, a rapid, selective and sensitive liquid chromatography-tandem mass spectrometry method for quantification of phenibut in biological matrices has been developed. The method is based on protein precipitation with acidic acetonitrile followed by isocratic chromatographic separation using acetonitrile-formic acid (0.1% in water; 8:92, v/v) mobile phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…17,28,44,57,60,61,66 Among all these homogenization methods, rotating blade is the most commonly used one for brain tissue samples, due to its low cost and easy operation. 19,21,22,31,36,38,40,41,43,75,77,79,81,[84][85][86]90 However, extra attention needs to be paid to the cleanliness of the blades, otherwise contamination can be a possible issue with the traditional rotating blade homogenizer. Bead beating 15,55 and ultrasonication 8,[24][25][26]39 are both newer techniques that have the advantages of higher efficiency, higher throughput as well as lower chance of contamination when compared to the traditional grinding or rotating blade homogenization techniques, making these two new techniques more popular in recent studies.…”
Section: Homogenizationmentioning
confidence: 99%
See 2 more Smart Citations
“…17,28,44,57,60,61,66 Among all these homogenization methods, rotating blade is the most commonly used one for brain tissue samples, due to its low cost and easy operation. 19,21,22,31,36,38,40,41,43,75,77,79,81,[84][85][86]90 However, extra attention needs to be paid to the cleanliness of the blades, otherwise contamination can be a possible issue with the traditional rotating blade homogenizer. Bead beating 15,55 and ultrasonication 8,[24][25][26]39 are both newer techniques that have the advantages of higher efficiency, higher throughput as well as lower chance of contamination when compared to the traditional grinding or rotating blade homogenization techniques, making these two new techniques more popular in recent studies.…”
Section: Homogenizationmentioning
confidence: 99%
“…Due to the simplicity of the method, water has been the most commonly used homogenization media. 13,14,19,21,22,35,40,41,43,49,50,57,70,71,74,75,77,80,81,[84][85][86]88,90 In these methods, to one unit weight of brain tissue, at least one to two volumes of ice-cold water is add for homogenization, forming a homogeneous suspension of diluted brain tissue. In some studies, more water is added to yield a more diluted brain homogenate, which can be treated similarly to plasma or even serum samples in sample preparation, making it possible to use the same method for multiple sample species.…”
Section: Homogenizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that after intraperitoneal administration in mice, the acute median lethal dose (LD 50 ) of phenibut was 900 mg/kg [2], while the median effective dose (ED 50 ) of phenibut was 10 mg/ kg [6]. It was shown that phenibut crossed the blood-brain barrier, that it was present in rat liver, kidney, and brain tissue, and that it was excreted unmetabolized in the urine by glomerular filtration following intravenous administration to rabbits, rats, cats, and dogs [7]. Two studies reported dopamine metabolism activation after the administration of phenibut in rats and mice [8,9]; however, these findings have not been confirmed in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of drugs in animal brain tissue is common in the literature 48 58 to check their crossing of BBB. Various extraction techniques were employed for extraction of drugs either from brain homogenate alone 50 , 51 or from both animal plasma & brain extract 50 56 including direct precipitation 48 51 ; liquid-liquid extraction 52 56 , solid phase extraction 57 & QuEChERS based approach 58 . Moreover, direct precipitation was also used for simultaneous extraction of eight neurotransmitters from brain tissue 59 .…”
Section: Introductionmentioning
confidence: 99%